STRATEGI MARKETING PUBLIC RELATIONS DUA COFFEE DALAM MEMPERTAHANKAN EKSISTENSI DI TENGAH MARAKNYA KEDAI KOPI DI JAKARTA - AISYAH ANDRIANI CAHYANINGRUM, (2022)
The growth of modern coffee outlets is soaring and mushrooming in various regions, especially in Jakarta. The growth of modern coffee outlets has skyrocketed and mushroomed in various regions, especially in Jakarta. The number of coffee shops has tripled on average in the last three years, now reaching 3,000 to 8,000 outlets in Indonesia. Tight competition in the coffee shop industry at this time makes Marketing PR Dua Coffee required to be able to maintain its existence so that it remains crowded with customers and can continue to grow over time. This study aims to determine the PR Dua Coffee marketing strategy in maintaining its existence in the midst of the rise of coffee shops in Jakarta.The research method used by researchers is descriptive qualitative research method. There are five informants in this research based on the criteria determined by the researcher. This research uses Whalen's 7 Step Strategic Planning Proccess Theory. This research uses data collection techniques by conducting interviews with Dua Coffee Marketing Public Relations, Dua Coffee Operations Manager, Dua Coffee Staff and two loyal Dua Coffee customers. The results of this study indicate that Dua Coffee's MPR Strategy applies the Pull, Push and Pass strategy using the 7 Step Strategic Planning Process analysis by utilizing social media in providing information about promotions, brand recognition, partnerships and delivering persuasive messages. Strategic placement, friendly hospitality, homey feel and unique menu variations provided. Creating a good image to the audience is also by making various contributions to the community in the development of the coffee industry and disasters that are being experienced by the audience. This is done in order to maintain the existence of Dua Coffee in the midst of the rise of coffee shops in Jakarta.